2012
DOI: 10.1260/0263-0923.31.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 6-Degree-of-Freedom Chassis Whole-Body Vibration in Mobile Heavy Vehicles Used in the Steel Making Industry

Abstract: Whole-body vibration (WBV) of mobile machines used in the steel making industry has not previously been quantified in six-degrees-of-freedom (6DOF). The purpose of this paper was to quantify 6DOF vibrations during the daily operating tasks of 5 commonly used mobile machines types used in the steel making and metal smelting industries. Vibration data were recorded from the chassis of five commonly used mobile machines using a MEMSense MAG3 triaxial accelerometer & gyroscope (MEMSense, SD, USA), and analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…In our phase one field data collection, VTV values for slag pot haulers ranged between 1.7-2.6 m/s 2 [15,16] whereas in the current work, the slag pot hauler with the new seat installed ranged between a minimum of 0.356 and a maximum of 0.956 m/s 2 which was an improvement. The slag pot hauler comfort levels from our previous field study placed in the top two categories of discomfort (Very Uncomfortable and Extremely Uncomfortable) [15,16] whereas the slag pot hauler with the new seat installed placed in the second lowest discomfort rating (Fairly Uncomfortable).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In our phase one field data collection, VTV values for slag pot haulers ranged between 1.7-2.6 m/s 2 [15,16] whereas in the current work, the slag pot hauler with the new seat installed ranged between a minimum of 0.356 and a maximum of 0.956 m/s 2 which was an improvement. The slag pot hauler comfort levels from our previous field study placed in the top two categories of discomfort (Very Uncomfortable and Extremely Uncomfortable) [15,16] whereas the slag pot hauler with the new seat installed placed in the second lowest discomfort rating (Fairly Uncomfortable).…”
Section: Discussionmentioning
confidence: 51%
“…Results from the field and the laboratory studies have been reported previously [15][16][17]. For the current phase, the vibration results are presented in Table 2 while the Seating Questionnaire results are contained in Table 3.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations